Factor configurations impacting shareholder wealth in mergers and acquisitions of acquiring companies listed on the Johannesburg Stock Exchange - Christidoulou, Theo (University of Pretoria, 2017)
Mini Dissertation (MBA)--University of Pretoria, 2017.